Avaliação das características oclusais no sentido anteroposterior na dentadura decídua, em pacientes com ceceio anterior e/ou projeção lingual anterior, na emissão dos fones linguoalveolares [t], [d], [n] e [l] - Traya, Caled Hajar (2012)
This cross-sectional epidemiologic study, conducted in 220 Brazilian children, from male (100) and female (120) genders, during the complete primary dentition, enrolled in a public school, in São Paulo city, had as aim to evaluate the occlusal characteristics on its anteroposterior way and its interrelationships with the anterior lisping and/ or anterior tongue thrust, during the articulation of the lingua-alveolar phones [t], [d], [n] and [l]. All children from the sample were subjected to speech therapy assessment and to clinical examination of the occlusion on its anteroposterior way. The Mann-Whitney test was put into practice to make the comparison between the groups with and without speech change in relation to the age and the overjet and the Chi-Square test to make the verification of the possible associations between the speech pathology and the terminal relationship of the primary second molars (p0,05). Been used in this study, to associate with the terminal plane of the primary second molars, only children who showed symmetry between both sides right and left, totaling 192 children, with the following results: Vertical Plane 69,3%, Mesial Step 18,7% e Distal Step 12,0%. As for the phonetic deviations: 75% of the children didn’t show lisping and 25%, did; 66,8% of the children didn’t show tongue thrust and 33,2%, had. As for the association of the lisping and the tongue thrust with the type of the terminal relationship, it wasn’t found any significant results (p = 0, 91 e 0, 38, respectively). There was statistically significant difference between the tongue thrust and the interincisal trespass and the age sample (p = 0, 0127 e 0, 0232 respectively). It was concluded that phonetic deviations didn’t show significant relation with the type of terminal relationship of the primary second molars and most of the children with increased overjet showed tongue thrust during speech